1992
DOI: 10.1248/cpb.40.1500
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Activity of Porcine Neuromedin U-25 and Various Neuromedin U-Related Peptide Fragments on Isolated Chicken Crop Smooth Muscle.

Abstract: Contractile activity of porcine neuromedin U-25 (p-NMU-25) and various neuromedin U (NMU) peptide fragment amides was examined on chicken crop smooth muscle preparation. The relative activity (expressed as RA value) of p-NMU-25 to porcine neuromedin U-8 (p-NMU-8) was 5.51 +/- 0.09, and p-NMU-25 (15-25) was the most potent fragment with an RA value of 7.78 +/- 0.05. All C-terminal 11-peptide amides of rat, rabbit, and frog NMU peptides retained activity about three-fold higher than the corresponding C-terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 1 publication
3
11
0
Order By: Relevance
“…The longer COOH-terminally amidated porcine peptide (NmU-25) contains 25 amino acids, while the shorter peptide (NmU-8) is a result of proteolytic processing of NmU-25 at the Arg 16 -Arg 17 site and represents the amidated COOH-terminal 8 amino acids of the longer form. NmU was subsequently identified in many mammals, including humans (24), and the human gene encoding the NmU precursor peptide has been cloned (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer COOH-terminally amidated porcine peptide (NmU-25) contains 25 amino acids, while the shorter peptide (NmU-8) is a result of proteolytic processing of NmU-25 at the Arg 16 -Arg 17 site and represents the amidated COOH-terminal 8 amino acids of the longer form. NmU was subsequently identified in many mammals, including humans (24), and the human gene encoding the NmU precursor peptide has been cloned (25).…”
Section: Discussionmentioning
confidence: 99%
“…NmU-like immunoreactivity has since been detected in neurones in the mammalian brain and gastrointestinal tracts of various species (8 -10) and in the thyroid and endocrine cells of the pituitary gland (8,11). The smooth muscle-contracting effects of NmU are now well documented: NmU causes hypertension (7), can regulate local blood flow in the intestine (12)(13)(14), and exhibits contractile activity in various smooth muscle preparations in vitro, such as human ileum and urinary bladder (15), chicken crop (16), and rat stomach (17). In addition, complex effects on steroid secretion from the adrenal cortex have also been reported (18,19).…”
mentioning
confidence: 99%
“…These sequences may act to fold the peptide, holding it in a conformation that is more favorable for activity. Similarly, fragmentation of the NH 2 -terminal regions of NmU-25 from rabbit, pig, and frog demonstrates that the C-terminal 11-peptide amides retain contractile activity on chicken crop smooth-muscle that is at least three times more potent than their C-terminal 8-peptide amide equivalents (Okimura et al, 1992). This suggests a functional role for the three amino acids directly extending from the C-terminal octapeptide, despite considerable heterogeneity between species.…”
Section: Structure-activity Relationships Of Neuromedin Umentioning
confidence: 95%
“…Indeed, porcine NmU-25 is approximately three to five times more potent than porcine NmU-8 in mediating hypertensive effects in the rat and causing contraction of either rat uterine smooth-muscle or chicken crop smooth-muscle in vitro (Minamino et al, 1985a;Okimura et al, 1992). Similarly in the rat, intravenous porcine NmU-25 is a more potent mediator of mesenteric vasoconstriction (see Section V.B.)…”
Section: Structure-activity Relationships Of Neuromedin Umentioning
confidence: 99%
“…It was found that the neuromedin U-8 RIA system employing the antiserum ASH-15 was C-terminal specific, because the synthetic N-terminal analogs such as porcine neuromedin U-25 1,13) (Fig. 8) displaced the tracer,…”
Section: Smooth Muscle Contractile Activity and Immunochemical Cross-mentioning
confidence: 99%